CONSTRUCT VALIDATION INSTRUMENT OF ONLINE SHOPPING MODEL (Case Study : Electronic Ticket) - Renny Renny (Jurnal Ilmiah Ekonomi Bisnis, 2012)
The study objective is to develop measurement tool for online shopping model. Consideringmodel built using latent variables, research instrument deployed was questionnaire.Model was built using seven (7) latent variables such as perceived easy of use, perceived usefulness, attitude, intention, actual behavior, trust, and experience. Each of them are measured using 5, 5, 5, 5, 4, 5, 6, and 5 manifest variables (indicators)respectively. Perceived easy of use, perceived usefulness, intention, and actual behavior measurements were developed based on Klopping and McKinney, attitude and trust were developed based on Suh and Han, and experience based on Kim, Lee, and Kim. Questionnaire was distributed to 20 respondents. Validation test was performedusing Product Moment Pearson correlation. Test shows that perceived easy of use, perceived usefulness, attitude, intention, and experience were valid in which each of them measured with 5 manifest variables. Same evidence for actual behavior and trust variables which are also valid for 6 and 4 manifest variables respectively.Key Words : perceived easy of use and usefulness, attitude towards usefulness, inten tion to use, actual behavior, trust, and experience